The impact of supported employment and working on clinical and social functioning: results of an international study of individual placement and support. - Burns, T; Catty, J; White, S; Becker, T; Koletsi, M; Fioritti, A; Rössler, W; Tomov, T; van Busschbach, J; Wiersma, D; Lauber, C (2009)
BACKGROUND: Concerns are frequently expressed that working might worsen the mental health of people with severe mental illness (SMI). Several studies of Individual Placement and Support (IPS), however, have found associations between working and better nonvocational outcomes. IPS has been found to double the return to work of people with SMI in 6 European countries. AIMS: To explore separately associations between IPS, returning to work, and clinical and social outcomes. METHODS: Patients (n = 312) in a randomized controlled trial of IPS in 6 European centers were followed up for 18 months. RESULTS: There were no differences in clinical and social functioning between IPS and control patients at 18 months. Those who worked had better global functioning, fewer symptoms, and less social disability at final follow-up; greater job tenure was associated with better functioning. Working was associated with concurrently better clinical and social functioning, but this contrast was stronger in the control group, suggesting that IPS was better than the control service at helping more unwell patients into work. Working was associated with having been in remission and out of hospital for the previous 6 months. It was also associated with a slight decrease in depression and with being in remission over the subsequent 6 months. CONCLUSIONS: Concerns among clinicians about possible detrimental effects of working and supported employment have been misplaced. Although some of the associations found may have been selection effects, there is sufficient evidence of work having beneficial effects on clinical and social functioning to merit further exploration.